THE USE OF SNAKE AND LADDER GAME AS LEARNING MEDIA TO IMPROVE STUDENT’S SPEAKING SKILL IN INTRODUCING MYSELF MATERIAL TOWARD SEVENTH GRADE STUDENT OF SMPN 6 PAMEKASAN IN 2022-2023 SCHOOL YEAR - Tri Sulistini (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Speaking skill is a skill which always creates feeling of fear, embarrassed, reluctant and lack of self-confidence. Therefore, this skill is very difficult to be conducted in the classroom. Teachers should find some ways and techniques in presenting the speaking skill in their teaching and learning process so that the students gain the speaking competence. An alternative technique that may be used in conducting speaking skill in the classroom is by learning-playing technique or playing-learning technique. Teachers should select which games can be used in their classroom while they are teaching speaking skill. One suitable game to be presented and conducted in the speaking skill classroom is snake and ladder game. The students can play this game in pairs or in a small group. The purposes of this game is not only to train the students to speak up as many as possible but also to decrease the students’ feeling of fear, embarrassed, reluctant and lack of self-confidence since they do not need to do everything by their own, but their friend will always be ready to help them. Besides, the students can adapt, interact and communicate one and another in pairs or in a group. Finally, the students will have a great self-confidence to speak up, at least, in their own group. Hopefully, the students will gain their speaking competence through this game.